2008
DOI: 10.1242/dev.009688
|View full text |Cite
|
Sign up to set email alerts
|

Eomesodermin, a target gene of Pou4f2, is required for retinal ganglion cell and optic nerve development in the mouse

Abstract: SUMMARYThe mechanisms regulating retinal ganglion cell (RGC) development are crucial for retinogenesis and for the establishment of normal vision. However, these mechanisms are only vaguely understood. RGCs are the first neuronal lineage to segregate from pluripotent progenitors in the developing retina. As output neurons, RGCs display developmental features very distinct from those of the other retinal cell types. To better understand RGC development, we have previously constructed a gene regulatory network f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 43 publications
6
77
0
Order By: Relevance
“…6 A-H). Tbr2 is expressed in only a subset of RGCs (20), some of which eventually become intrinsically photosensitive RGCs (ipRGCs) (21). At E14.5, we observed a near complete loss of Tbr2 expression in DKO retinas, compared with wild-type retinas in which a subset of RGCs were Tbr2 + (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…6 A-H). Tbr2 is expressed in only a subset of RGCs (20), some of which eventually become intrinsically photosensitive RGCs (ipRGCs) (21). At E14.5, we observed a near complete loss of Tbr2 expression in DKO retinas, compared with wild-type retinas in which a subset of RGCs were Tbr2 + (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Nevertheless, we used some of these markers to examine whether the corresponding RGC subtypes were present in the P&I EE retina. Tbr2 (also known as "Eomes") is expressed in a subset of RGCs, from which the intrinsically photosensitive RGCs (ipRGCs) arise (47)(48)(49). At E14.5, by coimmunostaining for Tbr2 and Pou4f2, we observed that Tbr2 was expressed in equivalent numbers of RGCs in the P&I EE retina and the control retina, although its expression was almost completely absent in the Atoh7 tTA/tTA retina (Fig.…”
Section: Rgcs Generated By Ectopic Pou4f2 and Isl1 Have A Largely Normalmentioning
confidence: 82%
“…Their genes are among the most downregulated in Pou4f2 null retinas as determined by microarray analysis (Qiu et al, 2008). Eomes is a T-box transcription factor that similar to Pou4f1 and 3, is expressed in developing RGCs only upon their arrival into the RGC layer (Mao et al, 2008). Its expression is directly activated by Pou4f2 through a 5' enhancer and is completely downregulated in Pou4f2 null retinas (Mao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Eomes is a T-box transcription factor that similar to Pou4f1 and 3, is expressed in developing RGCs only upon their arrival into the RGC layer (Mao et al, 2008). Its expression is directly activated by Pou4f2 through a 5' enhancer and is completely downregulated in Pou4f2 null retinas (Mao et al, 2008). Conditional inactivation of Eomes causes a 30% decrease in RGC number and optic nerve size, reduced and disorganized RGC axon myelination, and increased apoptosis (Mao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation